Postoperative Rehabilitation and Return to Sport Following Multiligament Knee Reconstruction - Jill Monson, P.T., O.C.S; Jon Schoenecker, P.T., O.C.S; Nicole Schwery, M.S., C.S.C.S; Jamie Palmer, P.T., S.C.S; Ariel Rodriguez, M.S; Robert F. LaPrade, M.D., Ph.D (Elsevier, 2022)
Multiligament knee injuries (MLKIs) are debilitating injuries that increasingly occur in young athletes. Return to sport (RTS) has historically been considered unlikely due to the severity of these injuries. Reporting in the literature regarding objective outcomes following MLKI, including RTS, is lacking, as are clear protocols for both rehabilitation progressions and RTS testing. RTS following MLKI is a complex process that requires an extended recovery duration compared to other surgery types. Progressions through postoperative rehabilitation and RTS should be thoughtful, gradual, and criterion based. After effective anatomic reconstruction to restore joint stability, objective measures of recovery including range of motion, strength, movement quality, power, and overall conditioning guide decision-making throughout the recovery process. It is important to frame the recovery process of the athlete in the context of the severity of their injury, as it is typically slower and less linear. Improved reporting on objective outcomes will enhance our understanding of recovery expectations within this population by highlighting persistent deficits that may interfere with a full recovery, including RTS.